CHANGES ON THE SWEETS MARKET IN POLAND SINCE 2005. ON THE EXAMPLE OF COLIAN HOLDING SA (FORMERLY JUTRZENKA SA), ZPC MIESZKO SA AND WAWEL SA. (Research Bulletins of the Faculty of Economic Sciences, 2022)
The aim of the article is to discuss the changes on the Polish confectionery market since 2005. The analysis covered three companies: Colian Holding SA (formerly Jutrzenka SA), ZPC Mieszko SA and Wawel SA. The confectionery market in Poland has been developing intensively since 2005. The increase in the consumption of sweets per capita in Poland encouraged the introduction of new innovative products with exotic ingredients. The confectionery market in Poland was highly competitive, which forced considerable investments in marketing. The situation changed in 2020. Due to the coronavirus pandemic, the revenues of confectionery producers began to decline, Covid also had an impact on  consumer behavior.
Keywords: confectionery market, consumer trends, economic and financial analysis, enterprise, pandemic